THEORETICAL FOUNDATIONS OF THE DIALECTICS OF A HEALTHY LIFESTYLE AND NATIONAL HEALTH VALUES IN THE CONTEXT OF GLOBALIZATION - Abdullayev, Sodiqjon Mahmudovich (Oriental Journal of History, Politics and Law, 2025)
This article analyzes the theoretical factors through which globalization affects the concept of a healthy lifestyle and national health values. The study examines the philosophy of health, cultural practices of living, systems of ecological and ethical values, the socio-health status of society, and issues of cultural identification based on theoretical and philosophical approaches.